Development Of Smart Home System Using Arduino With Mobile Application - Ab Hadi, Nik Azran; Manimaran, Vasantha Kumaran; Mohd Annuar, Khalil Azha; Harun, Mohamad Haniff; Mohd Ab Halim, Mohd Firdaus; Mohamad Sapiee, Mohd Razali (MALTESAS, 2018)
Smart home system is getting more popular and widely used in many houses worldwide.Use of human’s voices to control home apparatus can be viewed as new worldview in the Home Automation System.Due to the headway of remote’s innovation,there are some wireless connectivity developed, for example,global system for mobile communications (GSM), WiFi,ZigBee and Bluetooth.Each of the connectivity has their own exceptional characteristics and applications. Nowadays,the physically challenged and elderly people depends on other people to operate any appliances in the house and it is too risky for them as they can easily fall down while walking.Developing this type of system could help them to live independently and reduce the risk on elder people’s life.Besides that,home automation can also reduce the amount of energy used by the client or users.The complexity of the wiring for home automation is too high and the cost will be charged higher too.The basic is to make it financially affordable and simple to arrange,allowing more individuals to gain it for their home, work places and schools.Pushed on the intelligent and sorted out methods utilized as a part of building up a smart home system and security system.At the same time,find out how the electric component that will be used in this system and ensured that the components are suitable and economics.In addition,elaborates on how the overall operation of smart home system works.Other than that, analyse and discuss the result obtained from this system. Finally,concludes the overall system process and improvement required on smart home system using with mobile application system.A point by point explanation is given to the made outline and a future progress that may be directed under this field is recorded.